Feeding the Dead: Ancestor Worship in Ancient India, by Matthew R. Sayers - Brodbeck, Simon (Religions of South Asia, 2016)
Feeding the Dead: Ancestor Worship in Ancient India, by Matthew R. Sayers. New York: Oxford University Press, 2013. xvi + 188 pp., £64.00 (hb), £19.99 (pb). ISBN 978-0-19-991747-1 (hb), 978-0-19-989643-1 (pb).